Effect of preparation and reaction conditions on the performance of In/H-Beta for selective catalytic reduction of NOx with CH4. (August 2020) - Zhao, Jiuhu; Zhang, Gaige; He, Jiansheng; Wen, Zhengzhong; Li, Zhi; Gu, Tingkun; Ding, Ran; Zhu, Yongji; Zhu, Rongshu
Abstract: In/H-Beta catalyst was prepared by optimizing the support, concentration of ion exchange liquid and calcination temperature to investigate the effects of synthesis conditions on catalytic activity of selective catalytic reduction of NOx with CH4 . The results showed that the In/H-Beta catalyst exhibited the superior activity when concentration of exchange liquid was 0.033 M and calcination temperature was 500 °C, the NOx removal ratio could reach 97.6%. In addition, reaction conditions could affect the catalytic performance. When O2 concentration was 10%, CH4 :NO ratio was no less than one, space velocity was lower than 23600 h −1 and NO initial concentration was no more than 700 ppm, In/H-Beta could exhibit superior catalytic activity. Moreover, the catalytic performances of In/H-Beta catalysts were discussed after enduring H2 O or/and SO2 . This novel strategy could open the door for selective catalytic reduction of NOx with CH4 . Highlights: In/H-Beta exhibited superior catalytic activity for CH4 -SCR of NOx to N2 . Effect of preparation and reaction conditions on activity of In/H-Beta were studied. Optimal preparation conditions were 7 wt % In/H-Beta calcined at 500 °C. In/H-Beta presented superior catalytic activity under simulative reaction conditions. This novel strategy could open the door for CH4 -SCR of NOx .